Problems and challenges in teaching and learning speaking at advanced level - Aleksandrzak, Magdalena (Wydawnictwo Naukowe UAM, 2011)
The article deals with the problems of teaching and learning speaking, in particular those which are most relevant in the context of developing oral skills at the advanced level of foreign language proficiency. The complex nature of spoken discourse must be taken into account and reflected at each stage of the learning process. Thus, the article examines the difficulties connected with choosing the appropriate framework and approach and discusses the typical patterns of interaction in the foreign language classroom. It also examines forms of control and evaluation and suggests some speaking activities which seem most suitable for advanced language learners in the light of the above theoretical considerations.
Keywords: Speaking skill; Genre; Task; Interaction; Testing; Evaluation